Access to Health Service and Social Support Related to Self-Medication - Mishra, Sudhir; Suwannapong, Nawarat; Tipayamongkholgul, Mathuros; Aimyong, Natnaree (Journal of Nepal Health Research Council, 2020)
Background: In developing countries including Nepal, medicine is easy to purchase with or without prescription over the counter. People’s self-medication practice is a leading cause of antibiotic resistance. The purpose of this study was to assess self-medication practice and its influencing factors among rural people of Nepal. Methods: A cross-sectional survey was conducted from total 62 wards in rural Rolpa district of Nepal.The probability proportional to size was applied to select 6 wards, then 115 households from each ward was selected by applying systematic random sampling. Data collection was done by interviewing 720 household heads age 18 to 70 years old using a structured questionnaire in Nepal Results: The proportion of regular self-medication practice was 54.6%. Among them, 96.4% practiced self-medication when they got diarrhea/dysentery and 94.2% when they got a stomach ache. The factors associated with self-medication practice included gender (OR=2.24,95%CI=0.23-0.42), age (OR=5.59,95%CI=3.68-8.47), religion(OR=0.57,95%CI=0.42-0.77), family type (OR=4.00,95%CI=2.93-5.47), average income (OR=7.31,95%CI=5.04-10.56), decision making (OR=0.6,95%CI=0.44-0.82, health insurance(OR=1.64,95%CI=1.22-2.22), overall access to health service (OR=3.53,95%CI=2.55-4.90), and appraisal support(OR=2.24, 95%CI=1.66-3.02) Conclusions: Prevalence of self-medication in rural areas of Rolpa district was high among female, older people Accessibility to health service should be improved to reduce risk of self-medication practice. The health promotion related with benefit and side effect from self-medication are important for high risk group i.e. people over 30 years . Keywords: Access to health service; rural Nepal; self-medication; social support